ANALISIS SATUAN KEMAMPUAN LAHAN UNTUK EVALUASI PARIWISATADI KAWASAN RAWAN BENCANA KAPANEWON CANGKRINGAN - Pulungan, Widya Annisa Fitri; Permatasari, Afrinia Lisditya (Universitas Negeri Yogyakarta, 2023)
Implementation of spatial planning in an area is planned based on the physical condition of the environment. Kapanewon Cangkringan has tourism potential to be developed as a disaster mitigation-based tourism area which is used as a tourist center as well as education. Along with the rapid pace of development and the increasing number of tourists due to tourism activities, threats to natural resources and ecosystems are also increasing, so it is necessary to analyze land capability in Kapanewon Cangkringan. The methods used in this research are spatial data analysis (overlay), scoring and qualitative descriptive analysis. The purpose of this study is to determine the level of land capability and to determine the level of land capability and to determine the relationship between land capability and evaluation of tourism in disaster-prone areas in Kapanewon Cangkringan. The results obtained were Kapanewon Cangkringan divided into four land capability classes namely Low, Medium, Moderately High and Very High Development Capability classes with the most dominant development capability class being the Very High Development Capability Class. The link between land capability and evaluation of tourism in disaster-prone areas is that four out of fifteen tourist objects were identified as not in accordance with the level of land capability that had been analyzed. This is because, some of these tourist sites are in areas with low levels of development that should not be developed as tourism areas.